Kebijakan Pemerintah Daerah untuk Mengembangkan Industri Kreatif (Studi pada Industri Kecil Menengah di Bali) - Andy Krisna; Izzatusholekha Izzatusholekha; Azhari Aziz Samudra; Randi Purnama (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Bali is an area that has traditional weaving crafts and still survives amid the globalization of textiles. This study describes the implementation of the policy of using traditional woven fabrics in encouraging the development of small and medium weaving industries (IKM) in Bali. The research was conducted with a qualitative approach. Data is collected through literature review, documents, and observation. Research through literature study utilizes online media, statistical data, books, articles in journals, government websites, and trusted online media. The implementation of the policy on the use of traditional Balinese woven or endek fabrics has gone according to the government's expectations, in the form of purchasing woven products, training for new woven craftsmen, providing looms, and establishing weaving centers. However, there are still a number of obstacles to be faced, namely in the upstream section, the availability of raw materials still relies on outside Bali. Generations of craftsmen who are still lacking to meet the sudden market demand.